Patients’ and healthcare professionals’ experiences of malnutrition risk management in heart failure: a qualitative study - Mengdie Liu; Zhiteng Xiong; Yanjuan Xu; Qihui Shen; Xinglan Sun; Si Liu; Xi Chen; Xiaoyun Xiong (Frontiers in Nutrition, 2026)
Background Malnutrition risk is common among patients with heart failure (HF) and is associated with disease progression and adverse clinical outcomes. However, patients and healthcare professionals (HCPs) differ in their understanding of and responses to nutritional issues in HF, and early identification and ongoing management remain insufficient in clinical practice. Objective To explore the current perceptions and needs of patients with HF and HCPs regarding malnutrition risk management, thereby supporting the implementation of systematic clinical nutrition practices and enhancing the engagement of both patients and HCPs. Methods A descriptive qualitative study design was used. Using purposive sampling, 15 patients and 15 HCPs specializing in cardiovascular care and nutrition were recruited from the Department of Cardiovascular Medicine between September and October 2025 and participated in semi-structured interviews. Data were analyzed using thematic analysis. Results Four themes and 10 subthemes were identified from the interviews. (1) Understanding of malnutrition risk relied on everyday experience, including viewing symptoms as manifestations of the disease, judging nutritional status based on thinness and fullness, and differing understandings of the relationship between nutrition and HF; (2) uncertainty surrounded the identification of malnutrition risk in the context of HF, including interference from fluid status and inconsistent descriptions by HCPs of clinical screening and assessment practices; (3) nutritional communication struggled to achieve shared understanding, including differences in patients’ acceptance of terminology and the need for specific and actionable dietary guidance; and (4) malnutrition risk management was difficult to implement amid treatment requirements and real-world constraints, including balancing treatment goals with nutritional needs, difficulties with implementation at home, and gaps in professional support. Conclusion Malnutrition risk management in patients with HF is a continuous process encompassing risk understanding, clinical identification, effective communication, and implementation at home. Future efforts could strengthen dynamic, multidimensional nutritional risk assessment, promote communication in specific and practical terms relevant to daily life, and establish a continuous management pathway covering screening, assessment, referral, and follow-up through multidisciplinary collaboration and family involvement.